The Initial (Earliest) Report of Polymorphous Ventricular Tachycardia - Jani, Sonal (Ann Noninvasive Electrocardiol, 2006)
In these short historical notes, we describe the early history of polymorphic ventricular tachycardia. Polymorphous ventricular tachycardia was probably first noted in 1918 by Wilson and Robinson. In a publication describing complete heart block and ventriculophasic arrhythmia, they noted a tachyarrhythmia characterized by multiple extrasystoles of different types at a rapid rate. Also, we briefly discuss the earliest recognized torsades de pointes by Dessertenes in 1966 and the first description of catecholaminergic polymorphic ventricular tachycardia, by Reid in 1977.